Bambusaecoccus maolanensis, a new soft scale genus and species from China (Hemiptera: Coccomorpha: Coccidae) - Meng, Shitao; Xing, Jichun (Zootaxa, 2022)
A new genus of soft scale insect from Guizhou Province, China, Bambusaecoccus Meng & Xing gen. n., with Bambusaecoccus maolanensis Meng & Xing sp. n. (Hemiptera: Coccidae: Paralecaniini) as type species, is described and illustrated. The species was collected from bamboo, Bambusa (Dendrocalamopsis) sp. (Poaceae: Bambusoideae), under carton shelters built by the ant Crematogaster subnuda nigrosubnuda Özdikmen 2010 (Hymenoptera: Formicidae: Myrmicinae). Type specimens of the new species are deposited at the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).